Walter B. Wriston and daughter Catherine on her wedding day (Tufts Archival Research Center, 2008)
4.6 x 6.6. Walter B. Wriston with his daughter, Catherine, on her wedding day to Richard Quintal in the Church of Heavenly Rest (New York, N.Y.). The print and digital image were created from 'File2803' from the CD titled 'Walter B. Wriston Photographs - CD 1'.